Research Progress of the Liquid-Phase Exfoliation and Stable Dispersion Mechanism and Method of Graphene - Li, Liangchuan; Zhou, Ming; Jin, Long; Liu, Lincong; Mo, Youtang; Li, Xiao; Mo, Zhaoyou; Liu, Zhenzhao; You, Shengli; Zhu, Hongwei (Frontiers in Materials, 2019)
Graphene is a honeycomb hexagonal two-dimensional (2D) crystal nanomaterial with a thickness of only 0.334 nm. It has been widely used and studied because of its ultra-thin 2D nano-characteristics and excellent electrical, thermal, optical, and mechanical properties. With the continuous in-depth study of graphene, the liquid-phase dispersion of graphene has also achieved breakthroughs. This review summarizes the research progress of the liquid-phase exfoliation mechanism, exfoliation method, stable dispersion mechanism, and dispersion method of graphene in recent years. The research situations of the Hamaker constant theory in exfoliation mechanism and Hansen solubility coefficient theory in stable dispersion mechanism are mainly discussed. The shortcomings of the research are summarized and analyzes the graphene liquid phase dispersed in the important challenge in the future. The stable dispersion method of graphene is also summarized. In the future, the π-π interaction will be the most potential method for studying graphene stabilization.